Review Essay: Lullaby for Broadway? - Frisch, Walter (Current Musicology, 2006)
Latecomers to high culture, Americans are obsessed with identifying and canonizing indigenous art forms. In recent years, much of this attention has been lavished on jazz. One challenge in the study of both jazz and musical theater is locating the specific historical moment or the precise works in which the genres assume an identity, especially an ”American” one, distinct from their influences. For musical theater, those sources would include European operetta of the later nineteenth century-specifically the works of Johann Strauss, Offenbach, and Gilbert and Sullivan-as well as vaudeville, burlesque, revue, minstrel shows, variety shows, melodrama, and British musical comedy. In the first few years of the twentieth century, these traditions coalesced in the works of Victor Herbert (notably his Babes in Toyland, 1903) and George M. Cohan (his first big hit, Little Johnny Jones, 1904). Herbert (1859-1924) had been born in Ireland, raised in London, and trained in Germany, but arrived in the United States in 1886 and made his career in this country. Cohan (1878-1942) was a Yankee Doodle Dandy from the start, born, as the world knows, on (or near) July 4 in Rhode Island. The historiography of the American musical also exhibits a special tension, not shared by other art forms, between the whole and the part, between the shows (or movies) and the individual numbers. In general, the highest value has been placed on the “book” musical, one in which the elements are subsumed within an overall musico-dramatic design. Yet for many people, the songs, not the framework, embody the American musical. Indeed, although a musical is the product of many collaborators, we usually (as I have done above) identify it by its composer, or by composer and lyricist. Tin Pan Alley, the popular song industry that flourished in New York from the last decade of the nineteenth century through the first half of the twentieth, became intimately connected, but not completely coextensive, with staged shows. Harold Arlen never wrote a hit show (his music was featured in several successful movies), but is rightly acknowledged as one of the greatest composers of American popular music. Another tension in the scholarly treatment of the American musical, as in much writing about other American art forms (including the novel and film), arises between what might be called internalist and contextualist approaches. Internalists tend to look at the works (or individual songs) for their structural and expressive qualities. Contextualists seek to embed the works and their creators within the American social, cultural, and political milieu. Since many musicologists are formalists at heart (we fetishize our objects, as one ethnomusicologist tartly remarked some years ago), the internalist approach has dominated in writing on American musicals. Of course, these perspectives are not mutually exclusive: scholars and commentators will often move back and forth from work to context. The authors of the studies under review here handle these tensions in different ways according to their backgrounds and scholarly temperaments. Mark Grant describes himself as a writer and “composer [of] concert music and theater pieces”; his previous book was a history of classical musical criticism in America (1998). Steve Swayne is a young academic who received his PhD in 1999 and teaches at Dartmouth College; this book is a comprehensively revised version of his dissertation. Raymond Knapp is a senior musicologist at UCLA who has written extensively on late nineteenth- and early twentieth-century European concert music; his book has grown out of an undergraduate course that he teaches.